Creativity and Innovation in Business and Beyond : Social Science Perspectives and Policy Implications. - Mann, Leon (Taylor & Francis, 2011)
Creativity and Innovation in Business and Beyond illustrates the ways in which creativity spurs innovation - not only in the realms of business and management, where the innovation is regularly acknowledged and discussed, but throughout the social sciences. With contributions from experts in fields as far-flung as policy, history, economics, law, psychology, and education, in addition to business and management, this volume explores the manifold avenues for creativity and innovation within and across a multitude of disciplines.